Pengaruh Dewan Komisaris Independen dan Board Gender Diversity terhadap Integritas Laporan Keuangan pada Perusahaan Manufaktur - I Gede Nata Mintara; Dewa Ayu Eny Wulandari; Dewa Ayu Mas Putriari Nusantari; Ni Wayan Diah Puspita Sari; Anak Agung Bagus Dharma Putra Dewangga (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The integrity of financial statements is an important aspect in decision making by stakeholders, but there are still many cases of manipulation that reflect the low integrity of the company's financial statements. Financial statements are very important to ensure that the information presented in the report is accurate, relevant, and free from manipulation. This study aims to analyze the effect of the independent commissioners, and gender diversity of commissioners, of financial statements in manufacturing companies listed on the Indonesia Stock Exchange in 2023 - 2025. The population in this study was 204 manufacturing companies listed on the Indonesia Stock Exchange for the period 2023 - 2025. The number of samples used in this study was 182 companies multiplied by 3 years of observation to become 546 companies determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results of the study show that independent commissioners have a positive effect on the integrity of financial statements. The gender diversity of commissioners do not affect the integrity of financial statements.